Life and Relation beyond Animalization: Review of Richard Iveson, Zoogenesis: Thinking Encounter with Animals - Calarco, Matthew (Humanimalia, 2017)
Richard Iveson. Zoogenesis: Thinking Encounter with Animals. London: Pavement Books, 2014. 346 pp. $31.99 pb.